ANALISIS PERPUTARAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS DI BURSA EFEK INDONESIA - Willya, Willya; Efriyenti, Dian (SCIENTIA JOURNAL, 2021)
Food and beverage companies are experiencing very good development. A food and beverage company or other company can run smoothly so company may managed its working capital and liquidity properly to achieve predetermined goals. This researches aim determine effect of working capital turnover and liquidities on profitability in Indonesia Stock Exchange. Populations on that research are company on the food and beverage sector in the Indonesia Stock Exchange companies from 2015 to 2019, which consisted of 26 companies. The data collections techniques on these researches using the purposives sampling methods, namely the sampling techniques with certaining considerations, so the sample contained in this research were 9 companies. The research methods used are descriptive analysis and hypothesis testing. The resulting of the analys showed this working capital turnover has a negative but insignificant effect partially on Return on Assets (ROA). Current Ratio (CR) partially has a significant effect on Return On Assets (ROA). Simultaneous working capital turnover and liquidity (current ratio) have a significant effect on profitability (Return on Assets).